Toxicological effects of Napthalene on the early development of Zerrafish ((Danio rerio). - Vithushi, K.; Thulasitha, W.S. (University of Jaffna, 2020)
Polycyclic aromatic hydrocarbons and their derivatives constitute a large proportion present in diesel or crude oil and are identified as one of the major aquatic pollutants of which naphthalene (Nap) is one of the important chemicals. Therefore, the present study was carried out to identify the toxicological effects of Nap on the early developmental stages of a lower vertebrate model; zebrafish (Danio rerio). Healthy same-aged embryos (6 hours post fertilization –hpf) were obtained by induced spawning and utilized in this experiment. Nap was dissolved in 1% Dimethyl sulfoxide (DMSO) and the following concentrations were applied to respective groups (60, 40, 20, 10 and 5 mg/L). Egg water alone and DMSO with egg water were used as control. Percentage of mortality and developmental deformities were recorded at 24, 48, 72 and 96 hpf. All the treatments were done in triplicates. The results showed that LC50value in embryos for Nap based on Probit analysis was 19.91 mg/L. Embryos showed developmental deformities such as pericardial edema, yolk sac edema, yolk sac fluid accumulation, yolk sac turbidity, spinal cord bent, haemorrhage and bent tail upon Nap treatment. The minimum concentration of Nap that showed developmental deformities was 20 mg/L. Percentage of mortality increased with the increasing concentration of Nap. The results revealed that, Nap showed developmental toxicity on zebrafish embryos and the toxicity is concentration-dependent. Further studies are being conducted to confirm the developmental toxicity of Nap based on histological analysis.
Keywords: Naphthalene; Zebrafish; Embryo-toxicity; Malformation; Deformities